The impact of Urbanization on the Proliferation of Aedes Aegypti (Diptera: Culicidae) Mosquito Population in Dhaka Mega City, Bangladesh (Bangladesh Journal of Zoology, 2024)
The impact of urbanization on various parameters related to Aedes aegypti, the vector responsible for dengue transmission, was assessed in the present study. Extensive larval population surveys were conducted from May to December 2022 across different urbanization levels in Dhaka city. Our survey was conducted in three areas: Uttara (23°52’ N, 90°22" E), Jatrabari (23°42’ N, 90°25" E), and Keranigonj (23°69’ N, 90°37" E) that characterized urban, suburban, and rural settings, respectively. The urban areas represented highly populated regions with a high concentration of anthropogenic structures, while the suburban areas encompassed a mix of residential and natural landscapes. The rural areas consisted of predominantly natural habitats with minimal human intervention. The findings revealed significant variations in larval abundance, larval development, egg production, and longevity. Notably, the urban areas exhibited the highest larval abundance compared to the suburban and the rural areas. Furthermore, in urban settings, the larval instars demonstrated accelerated growth compared to their counterparts in the suburban and the rural environment. The urban locales also witnessed a greater number of eggs and female adults displayed an extended lifespan compared to the suburban and the rural areas. The cumulative effects of urbanization resulted in heightened larval abundance, faster developmental rates, increased egg production, and prolonged survival period. These factors collectively contribute to an elevated vector capacity of adult mosquitoes. Considering the potential impact of Ae. aegypti on public health, it is imperative to establish entomological surveillance and control strategies tailored to diverse urbanization gradients. Developing mosquito control policies become crucial, with a focus on preventative measures to manage Ae. aegypti mosquitoes effectively within urban structures.Bangladesh J. Zool. 52(2): 201-215, 2024